The force cycle of vacuum gasket seals - Roth, A; Inbar, A (Vacuum, 1967)
The method of “sealometry” recently developed by the authors for the analysis of gasket seals has shown that an appropriate representation of the force cycle of a vacuum gasket seal gives multilateral information on the factors influencing it. The present paper discussed the various types of force cycle and shows the analytical correlation between the shape of the cycle and the phenomena determining the sealing effect. A graphical method for plotting the releasing path of the cycle from the tightening path, and vice versa, is given. Experimental results are compared with calculated values. Standard parameters are proposed for describing the force cycle, and the most characteristic cycle shapes are presented. The use of the force cycle shapes are presented. The use of the force cycle in establishing the suitability of seals for special purposes (repeated opening, baking, cryogenic, etc) is discussed.